Ujian Sekolah sebagai Upaya Pemetaan Mutu Sekolah Dasar - Rogers Pakpahan (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2015)
This study aims to examine the role of school exams for mapping the quality of primary schools in the compulsory education. The method used in this study are a descriptive analysis of the implementation document school exams and the results of the monitoring and data processing descriptive analysis. The results showed that: 1) assessment by educators in the context of the learning process can not be used as the quality mapping material of elementary school because the tests used by educators not standard and not the same quality; 2) School Exam results can be used as the quality mapping material of elementary school because the exam using standard tests and are relatively similar between the educational unit; 3) the results of the mapping quality based on school exams can be used as a basis for improving the quality of education in primary school through policy intervention by stakeholders (each school, district/cities education offices, and provinces). The conclusion of study of school examinations can be used as a basis for mapping the quality of primary schools and based on the quality of these schools can be used as a basis for fulfilling the needs school facilities to improve the quality of education in the implementation of compulsory basic education. ABSTRAK Penulisan ini bertujuan untuk mengkaji peran ujian sekolah untuk pemetaan mutu sekolah dasar dalam rangka wajib belajar pendidikan dasar. Metode yang digunakan dalam kajian ini yaitu analisis diskriptif pada dokumen penyelenggaraan dan hasil pemantauan pelaksanaan ujian sekolah sedang pengolahan data dilakukan dengan analisis deskriptif. Hasil kajian menunjukkan bahwa: 1) penilaian oleh pendidik dalam rangka proses pembelajaran tidak dapat dijadikan sebagai bahan pemetaan mutu sekolah dasar karena tes yang digunakan pendidik tidak baku serta tidak sama kualitasnya; 2) hasil ujian sekolah dapat dijadikan sebagai bahan pemetaan mutu sekolah dasar karena dalam ujian menggunakan tes baku dan relatif sama antar satuan pendidikan; 3) hasil pemetaan mutu berdasarkan ujian sekolah dapat dijadikan sebagai dasar untuk meningkatkan mutu pendidikan di sekolah dasar melalui intervensi kebijakan oleh pemangku kepentingan (satuan pendidikan, dinas pendidikan kabupaten/kota, dan provinsi). Kajian ini menyimpulkan pelaksanaan ujian sekolah dapat dijadikan sebagai dasar pemetaan mutu sekolah dasar dan berdasarkan mutu sekolah tersebut dapat dijadikan sebagai dasar untuk pemenuhan kebutuhan/fasilitas sekolah untuk meningkatkan mutu pendidikan dalam rangka pelaksanaan wajar dikdas.